City of saints & thieves - Anderson, Natalie C. (G.P. Putnam's Sons, an imprint of Penguin Random House LLC, 2017)
Sixteen-year-old Tina and two friends leave Kenya and slip into the Congo, from where she and her mother fled years before, seeking revenge for her mother's murder but uncovering startling secrets.